Influence of Trust, Quality of Service and Value Perception of User Confidence on Mobile Banking Services (Case Study on BNI Palembang Branch Customers) - Ida Rosmalia Ekadany; Marlina Widiyanti; Muchsin Saggaf Shihab; Mohammad Adam (Institut Manajemen Wiyata Indonesia, 2022)
This study was conducted to determine the impact of trust, service quality, and value perception of user confidence in mobile banking services for BNI customers in Palembang. The population in this study is all customers who use mobile banking services at PT. Bank Negara Indonesia (Persero), Tbk Palembang Branch, with a sample of 100 people, will be distributed to active customers at Bank BNI Cabang Palembang in 2021-2022 using the purposive sampling method. Based on the results of multiple linear regret analysis that has been carried out shows that trust, service quality, and value perception have a positive and significant effect on confidence in users of mobile banking services for BNI Customers in Abang Palembang. Service features n mobile banking need to be added, especially to the increasingly diverse top e-wallet services. Display the balance amount when making transactions such as transfers or e-wallet top-ups. Quality of service, there is a crash when topping up an e-wallet and top-up credit. BNI needs to increase the capacity of visits and establish cooperative relationships with e-wallet providers or service providers to provide better services. Perception of value, there needs to be follow-up or evaluation regarding changes in mpin and transaction codes if mobile banking users move applications by logging in and resetting on other devices because the BNI mobile banking service feature has many regulations that are a bit difficult to feel for users who are around >40 years.